2002
DOI: 10.1046/j.1365-2559.2002.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of mesothelial and epithelial antibodies in distinguishing diffuse peritoneal mesothelioma in females from serous papillary carcinoma of the ovary and peritoneum

Abstract: Calretinin and Ber-EP4 are useful discriminant markers in distinguishing peritoneal mesothelioma in women from serous papillary ovarian and peritoneal carcinoma. The other mesothelial markers (thrombomodulin, cytokeratin 5/6, and CD44H) and carcinoma markers (polyclonal and monoclonal CEA, and Leu-M1) yielded a too low sensitivity for practical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
109
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 22 publications
5
109
3
1
Order By: Relevance
“…Although the utility of calretinin immunostaining in the diagnosis of mesothelioma was confirmed in subsequent studies, 3,7,9,10,35,36 only a few investigations on the expression of this marker in serous carcinomas have been published 1,2,20,34,37 (Table 3). In the present study, all of the mesotheliomas showed diffuse strong reactivity for calretinin, which confirms the findings of previous investigations, indicating that this marker is frequently expressed in these tumors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the utility of calretinin immunostaining in the diagnosis of mesothelioma was confirmed in subsequent studies, 3,7,9,10,35,36 only a few investigations on the expression of this marker in serous carcinomas have been published 1,2,20,34,37 (Table 3). In the present study, all of the mesotheliomas showed diffuse strong reactivity for calretinin, which confirms the findings of previous investigations, indicating that this marker is frequently expressed in these tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Most studies have primarily focused on the utility of this marker in discriminating between mesotheliomas and lung adenocarcinomas, 9,26,34,35,[41][42][43] while only a few have investigated its value in differentiating peritoneal epithelioid mesotheliomas from serous carcinomas. 1,2,44 The reported percentages of thrombomodulin expression in serous carcinomas have ranged from 2 to 35%, and for peritoneal epithelioid mesotheliomas from 33 to 74% 1,2,44 (Table 5). In the present investigation, 73% of the mesotheliomas and 4% of the serous carcinomas were thrombomodulin positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, except calretinin and Ber-EP4, markers such as podoplanin, thrombomodulin, cytokeratin 5/6, WT-1, B72.3, CD15, CEA, and CA19-9 are not helpful in the differential diagnosis of papillary serous carcinoma and malignant mesothelioma of the peritoneum due to the decreased sensitivity and/or specificity. 36,37 Recently, ER was reported to be positive in 93% of papillary serous carcinoma of the ovary and the peritoneum and PR was positive in 29% of these tumors. In contrast, ER and PR were reportedly negative in all malignant mesotheliomas of the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…These include mesothelioma-related markers (calretinin, WT-1, thrombomodulin, CK 5/6), 11,43 adenocarcinoma-related markers (CEA, Leu M1, B72.3, Ber EP4), 43 Wolffian-derived structures-associated markers (CD10, calretinin), Mü llerian papillary serous neoplasm-associated markers (WT-1, CA125); a sex-cord tumor-associated marker (inhibin), and markers useful in characterizing metastasis of unknown origin (prostate-specific antigen, prostate-specific acid phosphatase, CDX-2, TTF-1 and CK7/CK20 coexpression pattern). [44][45][46][47][48] Obviously, a judicious selection from the above comprehensive list is required based on the most likely differential diagnoses. Selected panels are summarized in Table 6.…”
Section: Immunohistochemistry Of Testicular and Paratesticular Tumorsmentioning
confidence: 99%